The Impact of Food Security Policies on the Welfare of Farmers in West Aceh Regency - Nurmayanti Nurmayanti; Vellayati Hajad (Social and Political Corner, 2026)
This study aims to analyze the impact of food security policies on farmer welfare in West Aceh Regency. This research uses a qualitative method with a case study approach. Data were collected through interviews, observations, and documentation, using purposive sampling involving farmers and relevant government institutions such as the Food Service and the Agricultural, Food Crops, and Horticulture Service. The results show that food security policies have contributed to maintaining food availability and improving food access at the regional level, as reflected in stable production and government support programs. However, their impact on improving farmer welfare remains limited and uneven. Structural constraints such as limited irrigation systems, uneven distribution of agricultural inputs and machinery, weak market connectivity, and limited access to production resources continue to affect farmers’ productivity and income stability. In addition, not all farmers have fully benefited from government assistance due to uneven implementation and limited access to information. This study concludes that food security policies in West Aceh Regency have not yet fully improved farmer welfare and require strengthening infrastructure, institutional coordination, and market access to achieve more effective and sustainable outcomes.